2006
DOI: 10.1016/j.jacc.2006.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Computed Tomography Myocardial Perfusion Imaging During Adenosine Stress

Abstract: Adenosine-augmented MDCT myocardial perfusion imaging provides semiquantitative measurements of myocardial perfusion during first-pass MDCT imaging in a canine model of LAD stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
149
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(152 citation statements)
references
References 33 publications
0
149
0
3
Order By: Relevance
“…A multicenter study by Jeetley et al (84) demonstrated that myocardial contrast echocardiography with vasodilator stress is comparable to stress SPECT in the detection of CAD. George et al (85) recently determined the accuracy of multislice CT to measure differences in regional myocardial perfusion during stress in a canine model of coronary artery stenosis, and found that stress myocardial perfusion CT provides semiquantitative measurements of altered myocardial perfusion. There are several important points that currently influence the expansion of cardiac MRI in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study by Jeetley et al (84) demonstrated that myocardial contrast echocardiography with vasodilator stress is comparable to stress SPECT in the detection of CAD. George et al (85) recently determined the accuracy of multislice CT to measure differences in regional myocardial perfusion during stress in a canine model of coronary artery stenosis, and found that stress myocardial perfusion CT provides semiquantitative measurements of altered myocardial perfusion. There are several important points that currently influence the expansion of cardiac MRI in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of clinical studies have explored the diagnostic performance of myocardial CTP, showing a good sensitivity and negative predictive value, with modest specificity and positive predictive value (34)(35)(36)(37). Most of these were single center, had small sample size, and used different reference standard modalities including ICA, SPECT, CMR perfusion, and FFR.…”
Section: Clinical Evidencementioning
confidence: 99%
“…George et al were among the first to perform a semi-quantitative assessment of myocardial CTP using SECT (35). By means of a combined definition of ICAderived stenosis ≥50% with a corresponding SPECT perfusion abnormality, in a pilot study, George et al demonstrated that combined CCTA and CTP had a sensitivity, specificity, positive predictive value, and negative predictive value of 86%, 92%, 92%, and 85%, respectively.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that myocardial perfusion can be depicted by looking at the differences between rest and stress imaging [16]. Furthermore, dynamic CT data acquisition has been used in attempts to calculate myocardial perfusion reserve.…”
mentioning
confidence: 99%